Sytematic Literature Review (SLR): Peran Pendekatan Psikologi Dalam Memahami Kesulitan Belajar Siswa - Istiqomah Eka Diyanti; Dase Erwin Juansah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Educational psychology plays an important role in the world of education. Educational psychology can be one of the solutions in overcoming students' learning difficulties in elementary school. In addition, it is necessary to increase teachers' understanding of educational psychology to create effective learning and overcome students' learning difficulties. This study uses the Systematic Literature Review (SLR) method to identify relevant articles. The results of this research show that educational psychology in elementary school learning is very important to help children learn and develop optimally. By understanding and applying psychological approaches, educators can create a conducive learning environment, develop effective learning strategies, and help children reach their full potential.